PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA KARYAWAN DENGAN MEDIASI KEPUASAN KERJA - Desy Eka Kartika Sari; Surachman Surachman; Kusuma Ratnawati (University of Merdeka Malang, 2018)
This study analyzes both of directly effects between implementation of Total Quality Management (TQM) on employee’s performance and indirectly effect through job satisfaction. Subjects of this study were all the employees sited on production department of PT. Setia Kawan Makmur Sejahtera Tulungagung. The sampling technique used is the simple random sampling with 152 respondents. Model analysis used is a structural model with the Partial Least Square (PLS). The result of this study reveal that the improving of TQM practices would led to increased both of employee’s job satisfaction and employee’s performance directly. Then, the higher of job satisfaction can also enhance the employee’s performance directly. The mediation test result show that job satisfaction have partial mediationg role in effect of TQM practices on employee’s performance. Moreover, the overall results implies that teamwork is the most important aspect in building a good relations among employees, so as to encourage the employee’s job satisfaction and ultimately improve the quality of employee’s performance. DOI : https://doi.org/10.26905/jbm.v5i1.2313